Coupled quantum Otto heat engine and refrigerator with inner friction - Türkpençe, Deniz; Altintas, Ferdi (Springer Science and Business Media LLC, 2019)
We investigate two coupled spins 1/2 in a magnetic field as the working substance of the quantum Otto cycle. In the quantum adiabatic strokes, finite-time parametric transformations are employed either in the coupling strength or in the magnetic field. The operation regimes, where the mode of the cycle is a refrigerator or a heat engine, are explored. The role of the total allocated time to the quantum adiabatic stages on the performance of the quantum Otto refrigerator and the heat engine is investigated in detail. The finite-time adiabatic transformations are found to increase the Shannon entropy which is quantum in origin. The effect known as the inner friction is found to negatively effect the performances of the quantum heat engine and the refrigerator. The strong frictional losses are also found to induce inactive operation regimes where the mode of the cycle is neither a refrigerator nor a heat engine.
Keywords: Quantum Otto cycle; Quantum heat engine; Inner friction; Quantum thermodynamics; Quantum refrigerator